Comparison of 920 MHz and 2.4 GHz Near Ground Electromagnetic Wave Pathloss Propagation Model for Wireless Sensor Network in Forest Environment Application - Galang P. N. Hakim; Rachmat Muwardi; Mirna Yunita; Diah Septiyana (InComTech : Jurnal Telekomunikasi dan Komputer, 2022)
A Wireless Sensor Network (WSN) system that uses wireless communication technologies occasionally experiences data loss when undertaking wireless data communication. This problem happens because of the WSN system being placed on top of the ground and surrounded by vegetation that adds more loss to the transmission. In order to avoid this problem, the wireless system design must meet its best performance. To build the best performing WSN system, electromagnetic wave behavior in the forest environment needs to be studied well. This paper investigates the electromagnetic wave behavior transmitted and propagated by a WSN node at less than 30 cm from the ground using a 920 MHz frequency. We have analyzed that low height (30 cm) and vegetation environments can also add more loss at about 30.96 dB to the free space pathloss model. The new 920 MHz (that adds 30.96 dB loss) model shows identical behavior to 2.4 GHz with an average difference of 12.24 dB. However, the 920 MHz model performs better, achieving an average RMSE of 1.06 compared with the 2.4 GHz model, which can only achieve an average RMSE of 4.92 compared with the 920 MHz measurement.